Cross-Cultural Examination of the False Consensus Effect - Choi, Incheol; Cha, Oona (Frontiers in Psychology, 2019)
This study explored the cultural differences in the false consensus effect (FCE) between Koreans and European Americans. Two studies adopted a traditional false consensus paradigm and investigated the relative magnitude of the FCE between the two cultures in three different categories of personal choices (Study 1) and behavioral choices involving hypothetical conflict situations (Study 2). The FCE was observed in both cultures and the effect tended to be stronger among Koreans than European Americans. However, the results from Study 1 also demonstrated that this cultural effect depends on the domain of choices. Cultural implications were discussed.